Human umbilical cord‐derived scaffolds for cartilage tissue engineering. Issue 8 (24th April 2019) - Safari, Fatemeh; Fani, Nesa; Eglin, David; Alini, Mauro; Stoddart, Martin J.; Baghaban Eslaminejad, Mohamadreza
Abstract: Since articular cartilage is an avascular tissue, it has limited self‐regeneration capacity after damage. Current methods for human bone marrow‐derived mesenchymal stem cell (hBM‐MSC) differentiation into cartilage result in tissues with a lower quality as compared to native articular cartilage. Decellularized biological scaffolds have the potential to provide appropriate signals, in order to support cellular retention, migration, proliferation, and differentiation. Given the high amount of collagen, hyaluronic acid (HA), and glycosaminoglycan (GAG) in umbilical cord, this tissue can be considered as an abundant natural biomaterial for tissue engineering applications. Human umbilical cord‐derived scaffolds were prepared, and the chondrogenic induction of hBM‐MSCs loaded onto the scaffolds was investigated. Gelatin‐based scaffolds as a commercial material was used as a control. The results show that hBM‐MSCs in tissue‐derived scaffolds have an increased expression of chondrogenic markers compared with gelatin, whereas there are no significant differences between the expression of hypertrophic and osteogenic markers between tissue and gelatin scaffolds. In conclusion, it is confirmed that umbilical cord‐derived scaffolds are able to provide a native environment for the cells and can promote cartilage differentiation. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 107A: 1793–1802, 2019.